A Statewide Comparison of Gang and Non-Gang Youth in Public High Schools. (July 2014) - Gebo, Erika; Sullivan, Christopher J.
Gang and non-gang youth are often considered distinct for the purposes of prevention and intervention; yet, research shows there are areas of overlap in their risk profiles. This study examines areas of overlap and differences using a statewide representative sample of high school youth from the Youth Risk Behavior Survey. Gang membership is treated as a predictor variable rather than as an outcome. Results from a latent class analysis show that gang members do not form their own group in the school setting. These findings are discussed in relation to prevention and intervention strategies in the school realm and beyond.